2020
DOI: 10.1002/pon.5607
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression in a cohort of 400 patients with pancreatic neoplasm attending day hospital for major surgery: Role on depression of psychosocial functioning and clinical factors

Abstract: Objective (1) To determine the prevalence and type of depressive symptoms at day‐hospital clinical evaluation, before undergoing major surgery in patients diagnosed with pancreatic neoplasm. (2) To analyze the association between depression and sociodemographic, clinical, and psychosocial variables. (3) To understand how coping strategies, perceived social support, and self‐efficacy might affect depressive symptoms in this cohort of patients. Methods Secondary data analysis collected during the baseline phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…As could be expected, we found high comorbidity between anxiety and depressive symptoms, showing that these clinical conditions frequently overlap, at least in this population [39] and both need to be considered in a screening evaluation during the day-hospital stay. A recent study by our group showed that patients, candidates for pancreatic resection [17], often present depressive symptoms related to demoralization and physical exhaustion, self-blame, denial and disengagement in coping. These are drivers of emotional distress and low self-efficacy, which in turn may contribute to triggering anxiety symptoms.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As could be expected, we found high comorbidity between anxiety and depressive symptoms, showing that these clinical conditions frequently overlap, at least in this population [39] and both need to be considered in a screening evaluation during the day-hospital stay. A recent study by our group showed that patients, candidates for pancreatic resection [17], often present depressive symptoms related to demoralization and physical exhaustion, self-blame, denial and disengagement in coping. These are drivers of emotional distress and low self-efficacy, which in turn may contribute to triggering anxiety symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…More details of sociodemographic and clinical frequency distributions are reported in Table 1 (column 1). At the time of admission to the Unit of General and Pancreatic Surgery, 41 (39%; 95% CI = 30.0-49.5) patients had clinically relevant levels of anxiety (STAI-S cut-off ≥ 45 [17]), among them 15 (14%) had severe anxiety, according to Ilardi's criterion [25]. The median score for state-anxiety STAI-S was 42 (range 33.5-49.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an overestimation of depressive disorders due to symptom overlap derived from somatic illnesses could partly explain this association (Rayner et al, 2011 ; Saracino et al, 2020 ). In cancer patients, SDSs are common (Del Piccolo et al, 2021 ), and being depressive, anxious, and fatigued are very specific depressive phenotypes in these patients (Schellekens et al, 2020 ). For depression screening in patients with cancer, somatic items showed a less discriminatory value than non-somatic ones, although they are still useful for mild/moderate depression detection, and ignoring them would lead to an underestimation of depressive syndromes (Grapp et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%